Linear and nonlinear multivariable feedback control : - Gasparyan, Oleg N. (John Wiley & Sons, Ltd., 2008)
Common in manufacturing, medicine, economics, communications and space systems, these control systems compare the ideal (input) and actual (output) signals and modify the behavior of the system according to standard. Gasparyan (State Engineering U. of Armenia) presents an original unified control theory of both linear and nonlinear multivariate feedback systems, also known as "multi-input multi-output" (MIMO) systems as a straightforward extension of classical control theory. With applications and examples, he describes traditional representations and stability analyses of linear MIMO systems, the performance and design of linear MIMO systems, one-frequency self-oscillation in nonlinear harmonically linear MIMO systems, forced oscillation and generalized frequency response characteristics of nonlinear MIMO systems, and absolute stability of nonlinear MIMO systems. This would work well as a professional reference and self-study guide as well as a course text.